Dealing With Territorial Boundaries, Space, and Time in Robinson Crusoe and Life of Pi Novels (Postcolonial Perspective) - Magdalena Baga (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2024)
Today's globalization eliminates time, space, distance, and national barriers. The two novels examined in this study implied those issues. The objective of this study is to analyze the territorial boundaries, spatial dimensions, and temporal aspects that evoke a profound impact in Robinson Crusoe and Life of Pi, employing a postcolonial perspective. Both of these works originated from a shared concept, specifically the theme of being stranded as a result of a shipwreck. However, these novels were written throughout distinct times spanning several centuries. Robinson Crusoe was published in the 18th century, whilst Life of Pi was published during the 21st century. The similar concept of "Castaway" does not imply the creation of an identical narrative. The level of precision in the portrayal of territorial boundaries, space, and time in these two works is noteworthy, but they exhibit certain distinctions. The narrative of Robinson Crusoe prominently features people embodying the roles of master and slave, hence highlighting the concept of social boundaries. Contrarily, Life of Pi explores the ambiguous nature of borders about territory, space, and time, as they are consistently subject to dispute. Consequently, the delineation of power dynamics between characters is likewise a matter of contestation. In conclusion, these two novels convey two different ideologies by territory, space, and time considered through the lens of post-colonialism. The span of centuries demonstrates the diversity of human interpretations of them. Robinson Crusoe conveys the idea that colonialism is inevitable. Meanwhile, Life of Pi interprets colonialism as cruelty.